Quantitative detection of Schistosoma japonicum cercariae in water by real-time PCR. - Yuen Wai Hung; Justin Remais (Public Library of Science (PLoS), 2008)
In China alone, an estimated 30 million people are at risk of schistosomiasis, caused by the Schistosoma japonicum parasite. Disease has re-emerged in several regions that had previously attained transmission control, reinforcing the need for active surveillance. The environmental stage of the parasite is known to exhibit high spatial and temporal variability, and current detection techniques rely on a sentinel mouse method which has serious limitations in obtaining data in both time and space. Here we describe a real-time PCR assay to quantitatively detect S. japonicum cercariae in laboratory samples and in natural water that has been spiked with known numbers of S. japonicum. Multiple primers were designed and assessed, and the best performing set, along with a TaqMan probe, was used to quantify S. japonicum. The resulting assay was selective, with no amplification detected for Schistosoma mansoni, Schistosoma haematobium, avian schistosomes nor organisms present in non-endemic surface water samples. Repeated samples containing various concentrations of S. japonicum cercariae showed that the real-time PCR method had a strong linear correlation (R(2) = 0.921) with light microscopy counts, and the detection limit was below the DNA equivalent of half of one cercaria. Various cercarial concentrations spiked in 1 liter of natural water followed by a filtration process produced positive detection from 93% of samples analyzed. The real-time PCR method performed well quantifying the relative concentrations of various spiked samples, although the absolute concentration estimates exhibited high variance across replicated samples. Overall, the method has the potential to be applied to environmental water samples to produce a rapid, reliable assay for cercarial location in endemic areas.